Implementation and Efficacy of Plyometric Training: Bridging the Gap Between Practice and Research. Issue 5 (May 2021) - Watkins, Casey M.; Storey, Adam G.; McGuigan, Michael R.; Gill, Nicholas D.
Abstract : Abstract: Watkins, CM, Storey, A, McGuigan, M, and Gill, ND. Implementation and efficacy of plyometric training: Bridging the gap between practice and research. J Strength Cond Res 35(5): 1244–1255, 2021—Plyometric training is an effective method for improving speed and acceleration. However, a gap seems to exist between research recommendations and practitioner's actual programs. Some reports suggest as many as 400 jumps per session, while anecdotally some strength and conditioning coaches are using as few as 15–40 jumps even with elite athletes. Thus, the purposes of this study were to obtain a clearer understanding of the practitioner's perspective on plyometric training strategies as compared to literary recommendations and to compare any trends across competition level or sport categories. An integrative mixed-methods model was used. Globally, 61 strength and conditioning practitioners completed an anonymous online survey, containing 5 sections: 1. Sport and coaching background information, 2. Plyometric training focus, 3. Periodization strategy, 4. Plyometric program details, and 5. Efficacy of plyometrics for sport performance. Questions included yes/no, multiple choice, Likert scale, percentage-based, and open-ended questions. The majority (70.5%) of respondents reported regularly implementing plyometric training and overwhelmingly (96.7%) reported positive athlete feedback surrounding its perceived efficacy. Findings confirmed that many practitioners regularly use significantly lower session volumes than previous literary recommendations ( p < 0.05). In addition, significant differences were noted in many program details across competition level and sport category including volume periodization, exercise choice, and plyometric intensity. Practitioners may want to reflect on these reported group differences when building training programs best suited for their athletes. Meanwhile, future research should consider these reported perspectives when formulating interventions in attempts of bridging the gap between practice and theory.